Why is the decline of routine jobs across Europe so uneven? - Holmes, C (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2014)
Previous SKOPE research has looked at the consequences of changes in the occupational structure of the UK on outcomes such as wage inequality (Holmes and Mayhew 2012) and occupational or earnings mobility (Holmes and Mayhew 2014). This Issues Paper looks in the broadest terms at how occupational structures have changed across the UK’s European neighbours, and what factors might be driving diverging experiences. For this, I consider the importance of educational attainment, unions, employment protection legislation, and minimum wages.